Konzeptualisierung der Emotionen ‚Überraschung‘ und ‚Wut‘ vor dem Hintergrund der konzeptuellen Metaphern GUT IST OBEN und SCHLECHT IST UNTEN - Jolanta Mazurkiewicz-Sokołowska (Colloquia Germanica Stetinensia, 2022)
The paper explores the question of the scope of the conceptual metaphors GOOD IS UP and BAD IS DOWN for emotions using the example of the emotions ‘surpriseʼ and ‘angerʼ. It discusses the thesis that positive emotions are localized upper and negative ones lower by the person. The starting point is the study by Marmolejo-Ramos et al. (2017) regarding the spatial localization of the emotion ‘surpriseʼ compared to the spatial localization of the emotions ‘joyʼ and ‘sadnessʼ. Using the example of the emotion ‘angerʼ, it is shown that the generalizing character of this thesis does not apply to all emotions. The paper presents three experiments conducted on Polish subjects. The results are discussed further with regard to the language-thought relation.